Cytotoxic effect of Ficus religiosa and Ficus benghalensis latex extracts on MCF-7 cell line - Tulasi, CDSLN; Narasu, M. Lakshmi; Saida, L. (International Journal of Scientific Research in Biological Sciences, 2018)
Plants from Ficus genus were selected for the present study to screen their cytotoxic activity against the chosen human breast cancer cell line MCF-7. Cells were seeded in the 96 well plate and were grown for 24 hrs ensuring the proper attachment and adequate growth of cells in each well, after which the plant solvent extracts were treated in five different concentration for 24hrs and triplicates were maintained. The evaluation was based on reduction of MTT (3- [4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide) by mitochondrial dehydrogenase of viable cells, which gives a blue coloured formazan product, measured by spectrophotometry and the percentage growth inhibition as well the concentration at which the cells were 50% viable (IC50) was calculated. The morphological changes at IC50 were taken photographs.